2018
DOI: 10.1016/j.bbmt.2017.12.481
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact and Burden of CMV Infection on the Use of Resources in Allogeneic Hematopoietic Cell Transplantation

Abstract: 1, 10 on control). All patients were transplanted in the outpatient setting and were admitted for management of sepsis. The endpoints assessed were length of stay from initial admission, readmission rate and length of hospital stay post readmission. Results: Twenty autologous and allogeneic HCT recipients were included after a MRD (n = 5), MUD (n = 3) Haploidenitcal (n = 8), and autologous (n = 4) transplant. Median time from transplant to sepsis diagnosis was 41 days in the control group, and 20 days in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…3 ). Three studies [ 17 , 29 , 33 ] support that CMV reactivation increases the risk of re-hospitalization, but two studies [ 25 , 36 ] found no association between CMV reactivation and re-hospitalization (Table 4 , Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…3 ). Three studies [ 17 , 29 , 33 ] support that CMV reactivation increases the risk of re-hospitalization, but two studies [ 25 , 36 ] found no association between CMV reactivation and re-hospitalization (Table 4 , Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%